Hyperreality and Simulacrum: Jean Baudrillard and European Postmodernism (European Journal of Interdisciplinary Studies, 2017)
The aim of this paper is to present and explore one of the most fundamental concepts of postmodernity, that is, Jean Baudrillard’s elaboration of the ideas of hyperreality and simulacrum that characterise today’s global consumer culture in which the image of the product is more significant that the product itself. Some attention has also been devoted to European postmodernism, Jean-François Lyotard’s concept of the postmodern articulated in his renown book, The Postmodern Condition, in particular, and the merging of high and popular cultures to form consumer culture of late capitalism.